Myocardial protection in chronic volume-overload hypertrophy of immature rat hearts - Karck, Matthias; Ziemer, Gerhard; Haverich, Axel (European journal of cardio-thoracic surgery, 1996)
OBJECTIVE: The benefit of cardioplegic cardiac arrest for protection of the immature myocardium is controversial. We therefore investigated the efficacy of (1) topical hypothermia alone (2) slow cooling by coronary perfusion hypothermia and (3) cardioplegic cardiac arrest plus topical cooling for protection of isolated immature rat hearts (age: 28 days). - METHODS: The isolated perfused rat heart model was used. Hearts were subjected to 8 h of global ischemia at 10 degrees C. The study was conducted after clinically relevant conditions of volume-overload myocardial hypertrophy had been established non-invasively by lifelong feeding of a diet low in iron. Parameters of left ventricular function, endothelial function, the metabolic status and myocardial injury were measured. - RESULTS: Topical hypothermia provided superior protection of hypertrophied hearts with recovery of maximum developed left ventricular pressure and rate of pressure rise at 41.2% +/- 22.3% and 34.5% +/- 20.7% (mean +/- standard deviation) of preischemic values (P < 0.05 versus slow cooling and versus cardioplegia plus topical hypothermia). The same pattern of recovery was observed among control hearts. The recovery of endothelial function following protection by topical hypothermia alone measured 55% +/- 41% in hypertrophied hearts and 62% +/- 37% in control hearts, but was not recordable in all other groups. In hypertrophied hearts post-ischemic myocardial high energy content was significantly improved with topical hypothermia alone for protection when compared to the other methods. Creatine kinase leakage during reperfusion did not differ significantly among the experimental groups. - CONCLUSION: Rapid cooling by topical hypothermia along provides superior protection of hypertrophied- and non-hypertrophied-immature rat hearts to additional slow pre-arrest cooling. Use of St. Thomas' Hospital cardioplegic solution No.2 (STS 2) does not improve protection, and even hinders functional recovery in hypertrophied immature hearts. Endothelial injury caused by cold asanguinous perfusates, including cardioplegia, interferes with the recovery of vascular function, which in turn, may limit mechanical function.